Terrisporobacter hibernicus sp. nov., isolated from bovine faeces in Northern Ireland. Issue 1 (10th January 2023) - Mitchell, Molly; Nguyen, Scott V.; Connor, Mairead; Fairley, Derek J.; Donoghue, Orla; Marshall, Helina; Koolman, Leonard; McMullan, Geoff; Schaffer, Kirsten E.; McGrath, John W.; Fanning, Séamus
Abstract : A new species of Terrisporobacter, a Gram-positive, spore-forming anaerobic group, proposed name Terrisporobacter hibernicus sp. nov., was isolated in Northern Ireland from bovine faeces collected in 2016. Designated as MCA3 T, cells of T. hibernicus sp. nov. are rod shaped and motile. Cells tolerate NaCl from 0.5 to 5.5 % (w/v), with a pH tolerance between pH 6 and 9. The optimal temperature for growth is 35–40 °C, and temperatures from 20 to 30 °C are tolerated. The polar lipid profile displays diphosphatidylglycerol, phosphatidylglycerol, two aminoglycolipids, one glycophospholipid, one aminolipid, three glycolipids, five phospholipids and one lipid. No respiratory quinones are detected. The predominant fatty acid profile includes C16 : 0 at 22.8 %. Strain MCA3 T is positive for glucose and maltose acidification, as well as glycerol and sorbitol. The biochemical results from a VITEK2 assay of strain MCA3 T, Terrisporobacter petrolearius LAM0A37 T and Terrisporobacter mayombei DSM 6539 T are also included for the first time. The closed and complete genome of strain MCA3 T from a hybrid Oxford Nanopore Technology MinION/Illumina assembly reveals no evidence for known virulence genes. Draft genome sequencing of T. mayombei DSM 6539 T and T. petrolearius LAM0A37 T, as performed by Illumina MiSeq, provides reference genomes for these respective species of Terrisporobacter for the first time. DNA–DNA hybridization values (d4 ) of MCA3 T to Terrisporobacter glycolicus ATCC 14880 T, T. petrolearius LAM0A37 T and T. mayombei DSM 6539 T are 48.8, 67.4 and 46.3 %, with cutoff value at 70 %. The type strain for T. hibernicus sp. nov. is MCA3 T (=NCTC 14625 T =LMG 32430 T ).